1996
DOI: 10.1111/j.1530-0277.1996.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality in Membrane Fatty Acid Compositions of Cells Measured on Erythrocyte in Alcoholic Liver Disease

Abstract: It has been proven that the fatty acids of esterified phospholipids in the cell membrane play an important role in membrane fluidity. Our previous in vitro experiment indicated that the impairment of erythrocyte membrane fluidity might be largely because of the change in fatty acids. The aim of this study is to clarify changes of cell membrane fatty acids in more detail in relation to various stages and pathology of alcoholic liver disease. For the analysis, erythrocyte membranes were exploited on the assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…The decreased metabolites while the liver function is decompensated indicate that stearic acid and DHA may be potential biomarkers for decompensated cirrhosis. These results are in accordance with the results of a previous study wherein stearic acid decreased significantly in the erythrocyte cell membrane in the alcoholic liver cirrhosis (Shiraishi et al 1996).…”
Section: Identification Of the Differential Metabolitessupporting
confidence: 83%
“…The decreased metabolites while the liver function is decompensated indicate that stearic acid and DHA may be potential biomarkers for decompensated cirrhosis. These results are in accordance with the results of a previous study wherein stearic acid decreased significantly in the erythrocyte cell membrane in the alcoholic liver cirrhosis (Shiraishi et al 1996).…”
Section: Identification Of the Differential Metabolitessupporting
confidence: 83%
“…The finding of an increased AA concentration also in RBC membrane phospholipids indicates stable incorporation of this fatty acid into biological membranes. Although it was not possible to assess the levels of AA in platelet phospholipids due to thrombocytopenia, it is likely that changes in platelet membrane paralleled those observed in RBCs, thus resulting in enhanced TX production [29].…”
Section: Table 2 Plasma Lipids (A) and Phospholipids (B) And Rbc (C) mentioning
confidence: 99%
“…Change in the fatty acid composition due to ethanol ingestion is the result of CYP2E1-dependent lipid peroxidation and fatty acid metabolism [13] . Previous reports have shown that chronic alcohol consumption increases stearic acid (18: 0) and palmitic acid (16: 0) [14] .…”
Section: Discussionmentioning
confidence: 99%